The clinical utility of lung clearance index in early cystic fibrosis lung disease is not impacted by the number of multiple-breath washout trials - Rachel E. Foong; Alana J. Harper; Billy Skoric; Louise King; Lidija Turkovic; Miriam Davis; Charles C. Clem; Tim Rosenow; Stephanie D. Davis; Sarath Ranganathan; Graham L. Hall; Kathryn A. Ramsey (ERJ Open Research, 2018)
The lung clearance index (LCI) from the multiple-breath washout (MBW) test is a promising surveillance tool for pre-school children with cystic fibrosis (CF). Current guidelines for MBW testing recommend that three acceptable trials are required. However, success rates to achieve these criteria are low in children aged <7 years and feasibility may improve with modified pre-school criteria that accepts tests with two acceptable trials. This study aimed to determine if relationships between LCI and clinical outcomes of CF lung disease differ when only two acceptable MBW trials are assessed. Healthy children and children with CF aged 3–6 years were recruited for MBW testing. Children with CF also underwent bronchoalveolar lavage fluid collection and a chest computed tomography scan. MBW feasibility increased from 46% to 75% when tests with two trials were deemed acceptable compared with tests where three acceptable trials were required. Relationships between MBW outcomes and markers of pulmonary inflammation, infection and structural lung disease were not different between tests with three acceptable trials compared with tests with two acceptable trials. This study indicates that pre-school MBW data from two acceptable trials may provide sufficient information on ventilation distribution if three acceptable trials are not possible.